Where does the one-repetition maximum exist on the force-velocity relationship in squat? - Rivière, J. R.; Rossi, J.; Jimenez-Reyes, P.; Morin, J.-B.; Samozino, P. (International Journal of Sports Medicine, 2015)
The aim was to determine the position of the one-repetition maximum (1RM) squat point on the force-velocity (F-V) relationship obtained during squat jump (SJ). Ten healthy athletes performed a 1RM squat during which ground reaction force and lower-limb extension velocity were measured, and six loaded SJs to determine individual F-V relationship. The goodness of fit of the linear F-V relationship with or without the 1RM point was tested. The vertical and horizontal coordinates were determined relative to the theoretical maximal force (F0) and the highest loaded SJ (load of 44.5±4.6% 1RM). The goodness of fit of the individual F-V relationship did not differ with or without the 1RM condition, even if the 1RM point was slightly below the curve (-5±5%, P=0.018). The 1RM point can be considered as a point of the F-V relationship. The velocity (0.22±0.05?m.s-1) of the 1RM point corresponded to ~30% of the velocity reached during the highest loaded SJ. The force developed in the 1RM condition was ~16% higher than during the highest loaded SJ and ~11% lower than F0. This finding underlines the difference between F0 and the 1RM condition.